MicroRNA-18a-5p Suppresses Tumor Growth via Targeting Matrix Metalloproteinase-3 in Cisplatin-Resistant Ovarian Cancer - Quiñones-Díaz, Blanca I.; Reyes-González, Jeyshka M.; Sánchez-Guzmán, Victoria; Conde-Del Moral, Isabel; Valiyeva, Fatma; Santiago-Sánchez, Ginette S.; Vivas-Mejía, Pablo E. (Frontiers in Oncology, 2020)
Cumulating evidence indicates that dysregulation of microRNAs (miRNAs) plays a central role in the initiation, progression, and drug resistance of cancer cells. However, the specific miRNAs contributing to drug resistance in ovarian cancer cells have not been fully elucidated. Aimed to identify potential miRNAs involved in platinum resistance, we performed a miRNA expression profile in cisplatin-sensitive and cisplatin-resistant ovarian cancer cells, and we found several differentially abundant miRNAs in the pair of cell lines. Notably, miR-18a-5p (miR-18a), a member of the oncogenic associated miR-17-92 cluster, was decreased in cisplatin-resistant as compared with cisplatin-sensitive cells. Real-time PCR analysis confirmed these findings. We then studied the biological, molecular, and therapeutic consequences of increasing the miR-18a levels with oligonucleotide microRNA mimics (OMM). Compared with a negative control OMM, transient transfection of a miR-18a-OMM reduced cell growth, cell proliferation, and cell invasion. Intraperitoneal injections of miR-18a-OMM-loaded folate-conjugated liposomes significantly reduced the tumor weight and the number of nodules in ovarian cancer-bearing mice when compared with a control-OMM group. Survival analysis using the Kaplan-Meier plotter database showed that ovarian cancer patients with high miR-18a levels live longer in comparison to patients with lower miR-18a levels. Bioinformatic analyses, real-time-PCR, Western blots, and luciferase reporter assays revealed that Matrix Metalloproteinase-3 (MMP-3) is a direct target of miR-18a. Small-interfering RNA (siRNA)-mediated silencing of MMP-3 reduced cell viability, cell growth, and the invasiveness potential of cisplatin-resistant ovarian cancer cells. Our study suggests that targeting miR-18a is a plausible therapeutic strategy for cisplatin-resistant ovarian cancer.